Libertie eaudiobook - Greenidge, Kaitlyn (Recorded Books Inc., 2021)
The critically acclaimed and Whiting Award–winning author of We Love You, Charlie Freeman returns with Libertie, an unforgettable story about one young Black girl's attempt to find a place where she can be fully, and only, herself. Coming of age as a freeborn Black girl in Reconstruction-era Brooklyn, Libertie Sampson is all too aware that her purposeful mother, a practicing physician, has a vision for their future together: Libertie is to go to medical school and practice alongside her. But Libertie, drawn more to music than science, feels stifled by her mother's choices and is hungry for something else—is there really only one way to have an autonomous life? And she is constantly reminded that, unlike her mother, who can pass, Libertie has skin that is too dark. When a young man from Haiti proposes to Libertie and promises she will be his equal on the island, she accepts, only to discover that she is still subordinate to him and all men. As she tries to parse what freedom actually means for a Black woman, Libertie struggles with where she might find it—for herself and for generations to come. Inspired by the life of one of the first Black female doctors in the United States and rich with historical detail, Kaitlyn Greenidge's new and immersive novel will resonate with readers eager to understand our present through a deep, moving, and lyrical dive into our complicated past.